Targeting Non-V600 Mutations in BRAF: A Single Institution Retrospective Analysis and Review of the Literature - Hirra A. Chaudhary; Timothy L. Cannon; Arthur Winer (Drugs in R&D)
Abstract Background and Objective While successful treatment paradigms for BRAF V600 mutations have been developed, 10% of BRAF mutations are not at V600 and lack a standard treatment regimen. This study summarizes the current body of knowledge on the treatment of non-V600 mutations and reports a single institution experience. Methods We conducted a literature review to summarize relevant preclinical and clinical published data on the response of non-V600 mutations to targeted therapies. We performed a retrospective analysis of INOVA Schar Cancer patients registered in our Molecular Tumor Board database with non-V600 BRAF mutations who were recipients of targeted therapy and assessed their time to next treatment and best response. Results Published preclinical and clinical data have demonstrated limiting results in the response of non-V600 mutated cancers to targeted therapies. Response rates were variable for the major classes of BRAF mutations including class II and class III mutations as well as, BRAF fusions. Data collected from our INOVA cohort offered promising results with one patient achieving partial remission and two patients achieving stable disease. Conclusions This article reflects the current understanding of targeted therapies in non-V600 mutations. Further large-scale studies separating BRAF mutations based on their mechanism of activation will  expand our understanding.